(untitled) (Emancipação, 2025)
This article proposes to discuss the trajectories of young people and adolescents socially produced as “unrightful humans” because they are attributed with committing an infraction. Although young black and poor people are the most victims of lethal violence in Brazil, they carry the stigma of being perpetrators of this problem and personify the condition of social enemies, considered unworthy of the guarantee of human rights. This is research-(in)vention carried out with subjects fulfilling socio-educational measures or leaving the system in Ceará. Public security policies based on war and punitive voluptuousness take race and gender as the basis for their structuring. Along with this, territorial conflicts crystallize violent death as a seemingly inevitable destiny. Strategies for the daily re-existence of these subjects in the face of this scenario are also outlined, seeking to contribute to discussions about the fight to guarantee human rights in this social segment.